2007
DOI: 10.1007/bf02698085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium selenosulfate on restoring activities of selenium-dependent enzymes and selenium retention compared with sodium selenite in vitro and in vivo

Abstract: Sodium selenosulfate has been extensively used as a precursor of selenide ions in the preparation of nano Se-containing compounds. Its biological properties remain completely unknown. Sodium selenosulfate and sodium selenite were added to the medium of HepG2 cells and administered intraperitoneally at a dose of 0.1 mg Se/kg body weight to selenium-deficient mice, respectively. Both of the selenium compounds could increase the activities of glutathione peroxidase (GPx) and thioredoxin reductase (TrxR) in a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…One hundred Se-deficient mice were randomly divided into the following ten groups with 10 mice per group (in accordance to Table 3 ). The doses of Se were chosen according to the report by Peng 50 . Mice were fed a Se-deficient diet (<0.02 μg Se/g diet) during the experimental phase of the study.…”
Section: Methodsmentioning
confidence: 99%
“…One hundred Se-deficient mice were randomly divided into the following ten groups with 10 mice per group (in accordance to Table 3 ). The doses of Se were chosen according to the report by Peng 50 . Mice were fed a Se-deficient diet (<0.02 μg Se/g diet) during the experimental phase of the study.…”
Section: Methodsmentioning
confidence: 99%
“…A different form of selenium with significantly lower toxicity would make selenium modulation of cisplatin toxicity more practicable. A candidate has been identified in selenosulfate ( − SeS(═O) 2 O − , 7 ) which equally, with 6 , elevates the activity of glutathione peroxidase and thioredoxin reductase in the human liver hepatocellular carcinoma cell line, HepG2 . Conversely, the bioavailability of 7 in terms of increasing selenium accumulation and the formation of selenoenzymes was marginally but significantly less than that mediated by 6 in selenium‐deficient mice at nutritional doses .…”
Section: Anti‐cancer Potential Of Molecular Selenium Compoundsmentioning
confidence: 99%
“…A candidate has been identified in selenosulfate ( − SeS(═O) 2 O − , 7 ) which equally, with 6 , elevates the activity of glutathione peroxidase and thioredoxin reductase in the human liver hepatocellular carcinoma cell line, HepG2 . Conversely, the bioavailability of 7 in terms of increasing selenium accumulation and the formation of selenoenzymes was marginally but significantly less than that mediated by 6 in selenium‐deficient mice at nutritional doses . The utilization of 7 as the source of selenium within the dose range required for the moderation of cisplatin toxicity is the same as that of 6 , an important finding as 7 is significantly less toxic than 6 .…”
Section: Anti‐cancer Potential Of Molecular Selenium Compoundsmentioning
confidence: 99%
“…As to the biological effects of sodium selenosulfate, we previously reported that sodium selenosulfate increased the activity of glutathione peroxidase and thioredoxin reductase in HepG2 cells; however, the bioavailability of selenosulfate in terms of increasing selenoenzymes and selenium accumulation was slightly but significantly less than selenite in selenium-deficient mice at a nutritional dose [11]. In the present study, we describe its cytotoxic effect against HepG2, Caco2, and three kinds of leukemia cells.…”
Section: Introductionmentioning
confidence: 66%